The Interplay Between Environmental Strategy and Green Human Resource Management on Environmental Outcomes Mediated by Ocbe - ASRUNPUTRI, Aisyah Pia; ANGGIANI, Sarfilianty; ARAFAH, Willy (PT Keberlanjutan Strategis Indonesia, 2024)
Universities, as esteemed higher education institutions, are increasingly recognizing their responsibility to address environmental issues and prioritize environmental conservation. This is demonstrated by the establishment of the UI GreenMetric World University Ranking by the University of Indonesia, which serves as a clear indication of the university's commitment to environmental sustainability. The objective of this study is to investigate the mutually beneficial connection between environmental strategy and green human resource management (GHRM) in terms of their impact on environmental outcomes, which is mediated by organizational citizenship behavior toward the environment (OCBE). The study will focus on 5 private universities situated in the Jakarta region. The findings demonstrated a correlation between green stewardship initiatives, which encompass both environmental strategy and green human resource management, and environmental outcomes. The direct correlation between OCBE and environmental outcomes also yields positive results. Nevertheless, the OCBE did not play a mediating role in the connection between green stewardship initiatives and environmental outcomes.